Market Research and Target Market Segmentation in City’s External and Internal Environment - Bassey, Mbiatke Anthony; Rashid, Umi Kartini; Harun, Amran (Penerbit UTHM, 2020)
Marketing segmentation have to be massive enough to fulfil the financial necessity of the organization and its products. Segmentation can be picked primarily based on demographics, psychographic, behavioural or geographic place. The segmentation has to be reachable by way of promotional means. Customer contentment, consumer allegiance and consumer retention are critical intermediate goals for education carriers on their ride to higher economic success in the liberalized markets. (Christopher, Payne, & Ballantyne, 2013) suggest the use of segmentation as a way to improve client satisfaction, client loyalty and consumer retention.